Accountability vertical das empresas estatais brasileiras - Louzada, Sergio Vinicius (2010)
This present work investigates the vertical accountability of the Brazilian Federal State Owned Enterprises –SOE through the analyses of their websites. For this, the work analyzed the definition of accountability in order to create a model of analyses with three dimensions; 'Transparency', 'Financial Transparency', and 'Interaction and Participation'. and a corresponding set of variables both rated by a panel of specialists. The results show that only 56% of the SOEs have accountability information in their websites, and 34% didn’t have any kind variables for the analyses of accountability. These observation lead to the conclusion that there is still space for vertical accountability of the SOEs through their website.